1977
DOI: 10.1007/bf00312810
|View full text |Cite
|
Sign up to set email alerts
|

Myotonia not aggravated by cooling

Abstract: The effect of local cooling has been studied in 27 normal subjects, 8 cases of myotonia congenita, 5 of myotonic dystrophy and one of paramyotonia. Using the adductor pollicis we registered the compound muscle action potential, the isometric twitch force and the time to half relaxation, the maximum tetanic force and to time 3/4 relaxation. 1. In normal subjects the twitch force and maximum tetanic force decreased after cooling (Fig. 2). The amplitude of the action potential increased. 2. Myotonia congenita and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 15 publications
3
7
1
Order By: Relevance
“…Thus, in the presence of a concentration of 9-AC known to reduce Ga to values of 10% or less of control, the appearance of myotonic activity is reversibly controllable by altering the external Ca++ concentration or the environmental temperature. A recent clinical study has demonstrated a temperature dependency similar to that reported here for myotonic activity in patients with myotonia congenita [26].…”
supporting
confidence: 82%
“…Thus, in the presence of a concentration of 9-AC known to reduce Ga to values of 10% or less of control, the appearance of myotonic activity is reversibly controllable by altering the external Ca++ concentration or the environmental temperature. A recent clinical study has demonstrated a temperature dependency similar to that reported here for myotonic activity in patients with myotonia congenita [26].…”
supporting
confidence: 82%
“…In view of the results of Simoncini and Stuhmer [15], it is likely that depolarization prevents the development of myotonic contractions by inactivating the voltagedependant Na+ channels. The failure of 9-AC-induced myotonia to develop at low temperatures supports the results of Ricker et al [4] obtained in human myotonic patients, which showed that myotonic contractions of the adductor pollicis muscle reverted to normal when the muscle temperature was lowered. Myotonia was alleviated in humans at 20"C, but in the present study it was not possible to identify the precise temperature at which myotonia failed to develop.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the low temperatures referred to were not quantified. It may be for these reasons that they are in conflict with the results of the only objective study done in humans [4] and our own results reported here, both of which are the outcome of quantitative measurements.…”
Section: Normal Krebscontrasting
confidence: 83%
See 2 more Smart Citations